Determinants to optimize response to clopidogrel in acute coronary syndrome - Betti Giusti; Anna Maria Gori; Rossella Marcucci; et al (Dove Medical Press, 2010)
Betti Giusti, Anna Maria Gori, Rossella Marcucci, Claudia Saracini, Anna Vestrini, Rosanna AbbateDepartment of Medical and Surgical Critical Care, University of Florence, SOD Atherothrombotic Diseases, AOU Careggi, Florence, ItalyAbstract: The inhibition of platelet function by antiplatelet therapy determines the improvement of the survival of patients with clinically evident cardiovascular disease. Clopidogrel in combination with aspirin is the recommended standard of care for reducing the occurrence of cardiovascular events in patients with acute coronary syndromes undergoing percutaneous coronary intervention. However, major adverse cardiovascular events including stent thrombosis occur in patients taking clopidogrel and aspirin. A growing body of evidence demonstrates that high post-treatment platelet reactivity on antiplatelet treatment is associated with increased risk of adverse clinical events. Clopidogrel requires conversion to active metabolite by cytochrome P450 isoenzymes. The active metabolite inhibits ADP-stimulated platelet activation by irreversibly binding to P2Y12 receptors. Recently, the loss-of-function CYP2C19*2 allele has been associated with decreased metabolization of clopidogrel, poor antiaggregant effect, and increased cardiovascular events. In high risk vascular patients, the CYP2C19*2 polymorphism is a strong predictor of adverse cardiovascular events and particularly of stent thrombosis. Prospective studies evaluating if an antiplatelet treatment tailored on individual characteristics of patients, CYP2C19*2 genotypes, platelet phenotype, drug–drug interaction, as well as traditional and procedural risk factors, are now urgently needed for the identification of therapeutic strategies providing the best benefit for the single subject.Keywords: antiplatelet therapy, clopidogrel, cytochrome P450 2C19 loss-of-function polymorphism, major adverse cardiovascular events, percutaneous coronary interventions